Effects of Additives on the Fermentation Quality, In Vitro Digestibility, and Aerobic Stability of Amaranth (Amaranthus hypochondriacus) and Wheat Bran Mixed Silage - Qixuan Yi; Peng Wang; Meng Yu; Tianyue Zhao; Xinxin Li; Hongyu Tang (Fermentation, 2023)
This experiment investigated the effects of different additives on the fermentation quality, in vitro digestibility, and aerobic stability of amaranth and wheat bran (AWB) mixed silage. In this experiment, a two-factor (moisture content × additive) completely randomized experimental design was used, with amaranth as the raw silage material, and the moisture content was adjusted to 60%, 65%, and 70% using wheat bran. At each moisture content condition, the silage treatments included groups without any additives (control), with lactic acid bacteria (L), with cellulase (E), and with lactic acid bacteria and cellulase (M). Six replicates of each treatment were analyzed for fermentation quality, chemical composition, and in vitro digestibility of AWB mixed silage after 60 days of ensiling. The results showed that in the same L group, the pH and the lactic acid (LA) in the 60% moisture content (MC) group were lower and higher, respectively, than in the 70% MC group (p < 0.05). In the same E and M groups, the ammonia nitrogen to total nitrogen (AN/TN) in the 60% MC group was lower than that in the 70% MC group, and the in vitro crude protein digestibility (IVCPD) was higher than that in the 70% MC group (p < 0.05). At the same time, the aerobic stability of AWB mixed silage gradually decreased as the MC of the raw material increased (p < 0.05). Under 60% MC, the IVCPD and in vitro neutral detergent fiber digestibility (IVNDFD) in AWB mixed silage from the E and M groups were higher than those in the control group (p < 0.05). Under 60% MC, the pH and AN/TN in AWB mixed silage from the M group were lower than those in the control group (p < 0.05). Compared with the control under 60% MC, the aerobic stability of AWB mixed silage inoculated with L, E, and M increased by 33 h, 42 h, and 57 h, respectively. It was shown that the addition of M resulted in the best fermentation quality, in vitro digestibility, and aerobic stability of AWB mixed silage when the amaranth MC was 60%.